About products of interaction of holmium chloride and bromide with carbamide - L. Yu. Alikberova; D. V. Albov; P. S. Kibalnikov; G. A. Fyodorova; V. V. Kravchenko; N. S. Rukk (Тонкие химические технологии, 2012)
The synthesis and data of the study of new complexes of samarium bromides with carbamide, [Ho(Ur)4(H2O)4]Br3 (I), [Ho(Ur)6(H2O)2]Br3 (II) and [Ho(Ur)4Cl3] (III), by IR spectroscopy and X-ray diffraction analysis are presented. For these compounds, coordination with metal occurs through the oxygen atoms of the water and carbamide molecules. The coordination polyhedra for I and II are distorted tetragonal antiprisms. In III, we have found inner-sphere coordination of four carbamide molecules and three chloride ions (the coordination polyhedron is a pentagonal bipyramid). The coordination of four carbamide molecules in I-III does not change their planar structures, but in II two carbamide ligands are distorted. Many hydrogen bonds are observed in the structures of complexes I-III.